(untitled) (University of Thi-Qar Journal for Engineering Sciences, 2025)
This article does not merely focus on studying the effectiveness of bladeless turbines and explainjng the reasons why they are small in height and diameter; it also discusses the reasons behind the shape changes and control of flow used. These aspects, together with a variety of different geometries with different degrees of surface roughness or lift above obstructions, contribute to maximizing energy production as the wind speed is increased at higher altitudes and the drag losses are minimized at lower altitudes. Moreover, it should be mentioned that due to the peculiar design of bladeless turbines, the turbines can take advantage of the exposed airflow at the boundary layer of surfaces, which forms a distinct effect when compared to other geometries. Blades do not exist in bladeless designs as opposed to conventional turbine wind turbines. Rather, they can be developed to vibrate or lose vortices in the presence of the wind, and this is an improvement of the present wind power technology. Moreover, a bladeless turbine comes with greater advantages than the conventional turbine because it is able to be used in urban areas where it does not impede by the development and well-being of people.